Yahoo Web Search

  1. Sort by

  1. a). By different formula LHS = cos(90)*cosA - sin(90)*sinA cos(90) = 0 sin(90) = 1 so LHS... angle formula sin(2x) = 2sin(x)cos(x) therefore RHS = 1 + sin(2x) = LHS

    2 Answers · Science & Mathematics · 09/06/2011

  2. Method - 1 ...................... On LHS, writing tan as ( sin / cos ), and taking...tan (45°-x) = (1-t) / (1+t). Hence, on the LHS ... Numerator = [ (1+t) / (1-t) ] - [ (1-t...

    3 Answers · Science & Mathematics · 23/04/2010

  3. 1. LHS = sinx cosx tanx - 1 = sinx cosx (sinx/cosx) - 1 = sin²x - 1 = -(1 - sin²x) = - cos 2x = RHS Hence proved 2. LHS = sin²x(cos²x/sin²x + 1) = sin²x[(cos²x + sin²x)/sin²...

    2 Answers · Science & Mathematics · 11/05/2010

  4. LHS = (1 + cos(x)) / (1 - cos(x)) = ((1 + cos(x))/cos(x)) / ((1-cos(x))/cos(x)) = (sec(x) + 1) / (sec(x) - 1) = (1 + sec(x)) / (sec(x) - 1) = RHS LHS = (sin(x) + tan(x)) / (cos(x) + 1) = (sin(x) + sin(x)/cos(x)) / (cos(x) + 1) = sin(x...

    1 Answers · Science & Mathematics · 03/06/2008

  5. LHS = cosh ( x + y ) = [e^(x + y) + e^(- x - y)]/2 RHS = cosh x cosh y + sinh x sinh y =[(e^x + e^-x)/2][(e^y + e^-y)/2] + [(e^x - e^-x)/2][(e^y - e^-y)/2] = (1/4)[e^(x + y) + e^(x - y) + e^(- x + y) + e^(- x - y)]   + (1/4)[e^(x + y) - e^(x - y) - e^(- x + y) + e^(- x - y)]  = (1/2)e^(x + y) + (1/2)e^(- x - y) = [e^(x + y) + e^(- x - y)]/2 so , LHS = RHS

    2 Answers · Science & Mathematics · 14/05/2014

  6. LHS = (cos²Θ/sinΘ) = cosΘ.cotΘ RHS = 2csc...cotΘ - cosΘ.cotΘ = cosΘ.cotΘ so LHS = RHS qed

    1 Answers · Science & Mathematics · 16/01/2013

  7. LHS sin^6(x) = [sin^2(x)]^3 = [1 - cos^2(x)]^3 [1 - cos^2(x)]^3 + cos^6(x) (1 - 3cos^2(x) + 3cos^4(x) - cos^6(x)) + cos^6(x) 1 - 3cos^2(x) + 3cos^4(x) RHS 1 - 3(1 - cos^2(x))cos^2(x) 1 - 3cos^2(x) + 3cos^4(x) LHS = RHS

    3 Answers · Science & Mathematics · 27/11/2012

  8. LHS = RHS 1 - cos²(x) = cos²(x) * tan²(x) * RHS..., by Pythagorean identity.. sin²(x) = 1 - cos²(x) = LHS I hope this helps!

    4 Answers · Science & Mathematics · 08/06/2011

  9. ... LHS = sin⁴ x + cos⁴ x = ( sin² x )² + ( cos²...

    1 Answers · Science & Mathematics · 08/08/2010

  10. ////////// LHS= (1-cos^2x+2cosx-1)/(2-cosx)(cosx+1) =cosx(2-cosx)/(2-cosx)(cosx+1) =cosx/(cosx+1) RHS=1/(1+(1/cosx)) =cosx/(1+cosx)=LHS

    1 Answers · Education & Reference · 22/04/2009

  1. Ad
    related to LHS
  1. Try asking your question on Yahoo Answers